Expanding desistance theories through the integration of offender strategies. Issue 1 (1st January 2021) - Williams, Gemma C.; Schaefer, Lacey
ABSTRACT: Existing theories of desistance can be loosely divided into two perspectives: socio-situational theories identify how life-course events and the social environment facilitate desistance, while subjective theories focus on individual differences in achieving desistance. Although both groups of theories receive empirical support, socio-situational frameworks are criticised for neglecting the processes which underpin them, while subjective explanations are criticised for overlooking the influence of opportunity structures in restricting offender agency. The current study aims to bridge this theoretical gap by inserting an action element of desistance. Semi-structured interviews were conducted with 53 probationers and parolees, asking them about their experiences with supervision and their efforts to comply with their order and desist from crime. A thematic analysis of the data uncovered four purposive actions that the participants use to avoid reoffending: (1) isolation, (2) knifing off antisocial peers, (3) prosocial activities and associations, and (4) getting clean. Our participants cited parenting and conventional goals as their main motivating factors, while the barriers to their desistance strategies included labelling, order conditions, and unemployment. Based on their reflections of their efforts to go straight, we suggest that desistance strategies mediate (ex-)offenders' motivation to desist and the structural conditions imposed upon them.